2017
DOI: 10.3390/su9040598
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Residents’ Preferences of the Land Use Program Surrounding Forest Park, Taiwan

Abstract: This paper aims to build up a preference function to evaluate the public benefits of the type of agricultural farming, biodiversity, water provisions, land use type, ecotourism modes, and a monetary attribute (willingness to pay and willingness to work) associated with an ecosystem service and land use program in a forest park. This study used choice experiments to build a random utility model, analyze the average preference for the above land use attributes based on the conditional logit (CL) and used a laten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…Meanwhile, the Forestry Bureau began to promote the 'Plains Landscape Reforestation and Beautification Program' to release farmland for new purposes, creating opportunities for local communities to develop eco-tourism and outdoor recreation locations [13]. This not only shows respect for the environment but has helped to create local employment.…”
Section: National Forest Recreation Areas In Taiwanmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, the Forestry Bureau began to promote the 'Plains Landscape Reforestation and Beautification Program' to release farmland for new purposes, creating opportunities for local communities to develop eco-tourism and outdoor recreation locations [13]. This not only shows respect for the environment but has helped to create local employment.…”
Section: National Forest Recreation Areas In Taiwanmentioning
confidence: 99%
“…The yea-saying bias in a traditional CVM design means that the respondents have a tendency to choose the option indicating 'yes' to express their opinions in place of their true preferences [15]. Therefore, for the evaluation of non-market goods, authors have indicated over the past two decades that CE has efficiencies and advantages surpassing the CVM [1,6,[13][14][15][16]. Furthermore, the CE model can capture respondents' preferences for potential quality improvement programs [13,[17][18][19], disclose multiple attributes and levels from empirical results that can be incorporated into policy making, and generate useful information for budget allocations based on specific topics [13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations